Enabling Real-Time Business Intelligence 6th International Workshop, BIRTE 2012, Held at the 38th International Conference on Very Large Databases, VLDB 2012, Istanbul, Turkey, August 27, 2012, Revised Selected Papers - Castellanos, Malu.; Dayal, Umeshwar; Rundensteiner, Elke A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed conference proceedings of the 6th International Workshop on Business Intelligence for the Real-Time Enterprise, BIRTE 2012, held in Istanbul, Turkey, in August 2012, in conjunction with VLDB 2012, the International Conference on Very Large Data Bases. The BIRTE workshop series provides a forum to discuss and advance the science and engineering enabling real-time business intelligence and the novel applications that build on these foundational techniques. This volume contains 10 research papers, which have been carefully reviewed and selected from xx submissions.
Real-Time Business Intelligence in the MIRABEL Smart Grid System -- Data Mining in Life Sciences: A Case Study on SAPs In-Memory Computing Engine -- The Vivification Problem in Real-Time Business Intelligence: A Vision -- An On-Demand ELT Architecture for Real-Time BI -- Instant-On Scientific Data Warehouses: Lazy ETL for Data-Intensive Research -- Query Processing of Pre-partitioned Data Using Sandwich Operators -- A Visual Interface for Analyzing Text Conversations -- Live Analytics Service Platform -- Strategic Management for Real-Time Business Intelligence -- Pricing Approaches for Data Markets.
Keywords: Computer science; Database management; Information storage and retrieval systems; Information systems; Management information systems; Computer Science; Information Storage and Retrieval; Business Information Systems; Computer Appl. in Administrative Data Processing; Database Management